PENGARUH PEMANFAATAN ADOBE FLASH DALAM PEMBELAJARAN ENERGI DAN PERUBAHANNYA TERHADAP HASIL BELAJAR IPA SISWA DI SEKOLAH DASAR - Pawadi, Pawadi; Mering, Aloysius; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe main problem of this research is concerning the process of natural science learning focusing on the standards of competency of energy and its change (electricity subject) which is still conventionally taught. The main purpose of this research is to examine the extent to which Adobe Flash can improve students’ learning outcome. The design of this research is “One-Group Pretes-Posttest (O1 X O2) with observation and documentation used as data collection techniques. The analysis results show that: 1). The average score of pretest of learning energy and its change with adobe flash is 64 meaning that it is still far below the minimum passing score (70); 2). The average score of posttest of learning energy and its change with adobe flash is 92.33 meaning that it is far above the minimum passing score (70); 3). The range between pretest and posttest of learning energy and its change with adobe flash is 28,33. In other words, the posttest score is higher than that of the pretest. This also indicates that using adobe flash media could result in better learning outcomes for students, especially in learning about energy and its change. Next, effect size calculation yields the score of 2,04 and can be categorized as very high. In conclusion, the use of adobe flash media is highly effective for improving students’ learning outcomes. Keywords: Adobe Flash, Learning, Learning Outcome